Securing SQL Server DBAs Defending the Database - Carter, Peter A. (Apress, 2018)
Protect your data from attack by using SQL Server technologies to implement a defense-in-depth strategy for your database enterprise. This new edition covers threat analysis, common attacks and countermeasures, and provides an introduction to compliance that is useful for meeting regulatory requirements such as the GDPR. The multi-layered approach in this book helps ensure that a single breach does not lead to loss or compromise of confidential, or business sensitive data. Database professionals in today's world deal increasingly with repeated data attacks against high-profile organizations and sensitive data. It is more important than ever to keep your company's data secure. Securing SQL Server demonstrates how developers, administrators and architects can all play their part in the protection of their company's SQL Server enterprise. This book not only provides a comprehensive guide to implementing the security model in SQL Server, including coverage of technologies such as Always Encrypted, Dynamic Data Masking, and Row Level Security, but also looks at common forms of attack against databases, such as SQL Injection and backup theft, with clear, concise examples of how to implement countermeasures against these specific scenarios. Most importantly, this book gives practical advice and engaging examples of how to defend your data, and ultimately your job, against attack and compromise. What You'll Learn: Perform threat analysis Implement access level control and data encryption Avoid non-reputability by implementing comprehensive auditing Use security metadata to ensure your security policies are enforced Mitigate the risk of credentials being stolen Put countermeasures in place against common forms of attack.